2020
DOI: 10.1186/s13213-020-01543-2
|View full text |Cite
|
Sign up to set email alerts
|

Kerosene tolerance in Achromobacter and Pseudomonas species

Abstract: The aim of the present study was to investigate the tolerance of five new Achromobacter and Pseudomonas strains to kerosene and to establish if the production of several secondary metabolites increases or not when these bacteria were grown in the presence of kerosene. The biodegradation of kerosene by isolated bacteria was also investigated in this study. Methods: Five Proteobacteria were isolated from different samples polluted with petroleum and petroleum products. Based on their morphological, biochemical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Secondly, the immobilized enzyme had enhanced access to the substrate, resulting in a higher reaction rate. Finally, the immobilized enzyme was less susceptible to inhibition by inhibitors present in the culture medium (Huang et al 2012;Brena et al 2013;Stancu 2020).…”
Section: Detection Of Apoptosis In Hepg2 Cellsmentioning
confidence: 99%
“…Secondly, the immobilized enzyme had enhanced access to the substrate, resulting in a higher reaction rate. Finally, the immobilized enzyme was less susceptible to inhibition by inhibitors present in the culture medium (Huang et al 2012;Brena et al 2013;Stancu 2020).…”
Section: Detection Of Apoptosis In Hepg2 Cellsmentioning
confidence: 99%
“…1 A large group of bacterial species (Gram-positive and Gram-negative) has been identified as potential kerosene degraders, including Pseudomonas spp., Bacillus spp., Acinetobacter spp., Escherichia spp., Proteus spp., Serratia spp., Streptomyces spp., Arthrobacter spp., Gordonia spp., Brevibacerium spp., Burkholderia spp., Mycobacterium spp., Nocardia spp., Xanthomonas spp., Alcaligenes spp., Flavobacterium spp., Micrococcus spp., and Corneybacterium spp. 13,[16][17][18] Effective biodegradation is influenced by biological characteristics and environmental parameters that exist within polluted sites. 19 These include the physicochemical nature of hydrocarbon pollutants, 20 microbial population quality (size, single strain, and consortia), 21 presence of xenobiotic pollutants such as heavy metals, 1 and environmental parameters in polluted sites such as nutrients availability, range of temperature and pH, soil moisture, and oxygen.…”
Section: Microbiology Insightsmentioning
confidence: 99%
“… 1 A large group of bacterial species (Gram-positive and Gram-negative) has been identified as potential kerosene degraders, including Pseudomonas spp., Bacillus spp., Acinetobacter spp., Escherichia spp., Proteus spp., Serratia spp., Streptomyces spp., Arthrobacter spp., Gordonia spp., Brevibacerium spp., Burkholderia spp., Mycobacterium spp., Nocardia spp., Xanthomonas spp., Alcaligenes spp., Flavobacterium spp., Micrococcus spp., and Corneybacterium spp. 13 , 16 - 18 …”
Section: Introductionmentioning
confidence: 99%
“…To determine the number of heterotrophic, hydrocarbon-tolerant, hydrocarbon-degrading bacteria, and enterobacteria that exist in the analyzed samples the plate culture method was used [7]. From the samples, serial dilutions (10 -1 -10 -6 ) were made in phosphate saline buffer, which were then inoculated in Petri dishes with solid LB nutrient medium [10], to determine the total number of heterotrophic bacteria, solid LB nutrient medium supplemented with diesel fuel (5% v/v) for determining the number of hydrocarbon-tolerant bacteria, solid mineral medium [11] supplemented with diesel fuel (5% v/v) for determining the number of hydrocarbon-degrading bacteria, and solid EMB medium for determining the total number of enterobacteria. For each dilution, 2 repetitions were done.…”
Section: Microbiological Analysis Of the Samplesmentioning
confidence: 99%
“…It could be observed that over time the petroleum products that reached the basement underwent a degradation process due to the consortia of bacteria that metabolize petroleum hydrocarbons [6]. The spilling of petroleum and petroleum products into the soil results in a numerical increase in bacterial populations that use hydrocarbons as a carbon source, with a concomitant reduction in bacterial diversity and the predominance of species that tolerate and/or degrade hydrocarbons [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%